1999
DOI: 10.1038/sj.bjc.6690634
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cyclins A and D and p21(waf1/cip1) proteins in renal cell cancer and their relation to clinicopathological variables and patient survival

Abstract: SummaryWe have studied 118 renal cell carcinomas to analyse the expressions of cyclins A and D1 and p21 (waf1/cip1) , and their relationship to clinical and histopathological parameters as well as to clinical outcome. Cyclins A and D1 and cyclin-dependent kinase inhibitor p21 (waf1/cip1) were not expressed in normal renal tissue. Staining signals of cyclin D1 and p21 (waf1/cip1) were always nuclear but cyclin A was also expressed in the cytoplasm of the tumour cells. The mean (range) fractions of cyclin A, cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
45
0
4

Year Published

2002
2002
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 36 publications
10
45
0
4
Order By: Relevance
“…Nevertheless, the renal cell lines stand out as consistently maintaining CCND1 expression under hypoxia in contrast to all other types examined here and reported in the literature. Our findings are in agreement with clinical data that approximately 75% of RCCs expressed a higher level of CCND1 protein than the normal kidney cortex (Lin et al, 1998;Aaltomaa et al, 1999;Hedberg et al, 1999;Stassar et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, the renal cell lines stand out as consistently maintaining CCND1 expression under hypoxia in contrast to all other types examined here and reported in the literature. Our findings are in agreement with clinical data that approximately 75% of RCCs expressed a higher level of CCND1 protein than the normal kidney cortex (Lin et al, 1998;Aaltomaa et al, 1999;Hedberg et al, 1999;Stassar et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…In patients with RCC, there have been some reports suggesting that low cyclin D1 expression, high cyclin A expression, and high Ki-67 expression indicate a poor clinical outcome. 3,29,30 Renshaw et al 5 reported that there was a positive correlation between cyclin A and Ki-67, but neither of these proliferative markers was correlated with tumor grade or stage in 33 patients with RCC. In contrast, other investigators have reported that increased cyclin A is a powerful and independent, unfavorable prognostic marker and that increased cyclin D1 is a favorable prognostic marker in patients with RCC.…”
Section: Discussionmentioning
confidence: 99%
“…In each complete section, 1000 tumor cells were counted manually, and the percentage of positive cells was calculated. We referred to previously reported 3 and well-prespecified criteria regarding the immunohistochemical expression of p27 in various types of tumors and, accordingly, divided the tumors into a group that had p27 expression with a labeling index (LI) Ն 50% (high p27 expression) and a group that had p27 expression with an LI Ͻ 50% (low p27 expression). In addition, the tumors were divided into two groups with regard to the other cell cycle-related proteins: high expression (Ն 1%) and low expression (Յ 1%) for cyclin A, 3 high expression (Ն 10%) and low expression (Ͻ 10%) for cyclin D1, 4 and high expression (Ն 1%) and low expression (Ͻ 1%) for MIB-1.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations